High temperature erosion behavior of cast nickel base 73Ni–13Cr–4Sn–4Bi–Mo alloy. (12th June 2019) - Aravind Nagaraj, T; Babu, S P Kumaresh; Rajkumar, M; Mahendran, R
Abstract: 73Ni–13Cr–4Sn–4Bi–Mo alloy was casted in induction melting furnace to study its erosion behaviour. High temperature erosion study was performed in air jet erosion test equipment at 450 °C with different angle of impingements such as 45°, 60° and 90° and different velocities such as 59 m s −1, 92 m s −1 and 124.137 m s −1 based on the valve applications. Eroded sample characterisation was done with optical microscope (OM) and scanning electron microscope (SEM) with Energy Dispersive Spectroscopy (EDS) to study the mechanism of erosion. The erosive resistance of the material is directly related to the impact energy of the erodent and velocities and results shows that the velocity of the erodent to be maintained at lower than 92 m s −1 which results in low erosive rate irrespective to the all angle of impingements.